A retrospective single-center pilot study of the genetic background of the transplanted kidney - Anna Novotna; Klara Horackova; Jana Soukupova; Petra Zemankova; Petr Nehasil; Pavel Just; Ludek Voska; Petra Kleiblova; Silvie Rajnochova Bloudickova (PLoS ONE, 2025)
Introduction Renal cell carcinoma (RCC) is one of the most prevalent cancers in kidney transplant recipients (KTR). The hereditary background of RCC in native kidneys has been determined, implicating its clinical importance. Materials and methods This retrospective single-center pilot study aimed to identify a potential genetic predisposition to RCC of the transplanted kidney and outcome in KTR who underwent single kidney transplantation between January 2000 and December 2020 and manifested RCC of the transplanted kidney. Next-generation sequencing (NGS) based germline genetic analysis from peripheral blood-derived genomic DNA (gDNA) was performed in both the recipient and donor using a gene panel targeting 226 cancer predisposition genes. Results The calculated incidence of RCC of the transplanted kidney among 4146 KTR was 0.43%. In fifteen KTR and donors, NGS was performed. The mean KTR age at transplantation and the diagnosis of RCC was 50.3 years (median 54; 5–67 years) and 66 years (median 66; 24–79 years), respectively. The mean donor age at transplantation and graft age at RCC diagnosis was 39.7 years (median 42; 7–68 years) and 50.2 years (median 46; 20–83 years), respectively. The mean follow-up after RCC diagnosis was 47 months (median 39.1; 0–112 months). Papillary RCC was the most prevalent (n = 8), followed by clear cell RCC (n = 6) and unspecified RCC (n = 1). Thirteen RCCs were low-stage (pT1a/b) diseases, one was pT3, and one was of unknown stage. Most RCC was higher graded. No germline pathogenic cancer-predisposition variant was found in either KTR or donors except for several variants of uncertain significance. Conclusion RCC of the transplanted kidney is very rare. Germline cancer-predisposition testing has identified several variants of uncertain significance, but no germline genetic predisposition to graft RCC in KTR. Further research is needed to assess the clinical relevance of genetic testing for cancer risk in KTR.